The health impacts of coal use in China. Issue 5 (26th April 2018) - Finkelman, Robert B.; Tian, Linwei
ABSTRACT: Each year China burns as much coal as the rest of the world. The coal use results in many benefits such as electricity, industrial heat, coke for steel manufacturing, and many valuable chemical products. Unfortunately, coal use also results in environmental degradation and widespread and severe health problems. China is especially vulnerable to these problems because of the abundant coal deposits occurring in every Chinese province, the predominantly rural population, and the widespread use of domestic coal burning. The health problems are attributed to exposure to fine particulate air pollution (PM2.5 ), mobilization of trace elements such as arsenic, fluorine, selenium, and possibly mercury and the release of organic compounds from incomplete combustion of domestic coal fires. Inhalation of minerals such as quartz and pyrite has deleterious health impacts contributing to lung cancer in women and black lung disease in coal miners. The extensive uncontrolled coal fires in China may also be a source of health problems. The overall situation has improved in recent years as uncontrolled fires have been extinguished, improved coal-burning stoves are being introduced, and people are switching to alternative fuel sources. Nevertheless, more needs to be done to minimize the health consequences of coal use in China.